KUALITAS PENGALAMAN MEMODERASI KUALITAS PRODUK DAN HARGA TERHADAP MINAT PEMBELIAN ULANG KEMBALI (Studi Kasus Pada Shampoo Tresemme) - Surya Bintarti; Jessica Naomi Manurung; Yuliani; Fany Octaviana (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Beauty Standards Every country has different beauty standards, now many women are competing to have well-groomed and smooth hair. In maintenance of beauty, hair is one of the "crowns" of women that beautify a woman, therefore all women take care of their crown so that it is always healthy and beautiful. TRESemme owned by PT. Unilever, which is a packaged shampoo product, has not yet won a position in the Top Brand Awards. The distribution of packaged shampoo from various other competitors has affected the ranking and sales of shampoo, even though packaged shampoo has been circulating for a long time. The purpose of this study was to examine the effect of experience quality on repurchase intention which was moderated by product quality and TRESemme shampoo price. The research was conducted within the boundaries of the community area of West Java Province. The number of samples obtained by 101 respondents. Research shows the results that the quality of experience influences repurchase intention (revisit), the quality of experience which is moderated by product quality influences repurchase intention (revisit), and the quality of experience which is moderated by price also influences repurchase intention (revisit).